Imidazolidine Derivatives in Cancer Research: What is known? - da Silva Júnior, Auvani A.; da Rocha Pitta, Marina Galdino; de Oliveira Chagas, Mardonny Bruno; de Melo Rêgo, Moacyr J. B.; da Rosa, Michelle Melgarejo; da Rocha Pitta, Maira Galdino (Anti-Cancer Agents in Medicinal Chemistry, 2022)
It is well known that cancer is the second leading cause of death worldwide. Due to this fact, new results for the treatment of cancer are constantly being introduced and verified. Imidazolidine derivatives regulate cell cycle progression and DNA stability. Structurally, a heterocyclic nucleus favors a direct DNA interaction and therefore, control of the DNA replication process. This review aims not only to discuss the role of imidazolidines in cancer therapy but also explore the functionality of such agents in the future aspects of cancer prognosis and treatment. Convincing data from 1996 to 2021 has presented imidazolidine derivatives as a relevant therapeutic tool to modulate cancer progression and malignancy. Here we highlight these aspects in a variety of cell lines, cancer types, involving in vitro and in vivo techniques.
Keywords: DNA